Complex impact of remoteness on the incidence of myocardial infarction in Aboriginal and non-Aboriginal people in Western Australia - Katzenellenbogen, Judith; Sanfilippo, Frank; Hobbs, Michael; Briffa, Tom; Knuiman, Matthew; Dimer, Lyn; Thompson, Peter; Thompson, Sandra (Blackwell Publishing, 2012)
Objective: To determine the impact of remoteness on Aboriginal and non-Aboriginal myocardial infarction incidence rates in men and women of different ages. Design: Descriptive study. Setting: Western Australia. Participants: Incident cases of myocardial infarction in Western Australia from 2000–2004 identified from person-linked files of hospital and mortality records. Analysis was undertaken for Aboriginal and non-Aboriginal populations, separately and combined, by broad age group, sex and remoteness. Main outcome measure: Incidence of myocardial infarction. Results: In the combined analysis, age-standardised incidence was significantly higher for men in very remote areas (rate ratio 1.31: 95% confidence interval (CI), 1.19–1.45) and in women in both regional (rate ratio 1.12: 95% CI, 1.01–1.20) and very remote (rate ratio 2.05: 95% CI, 1.75–2.41) areas. Aboriginal rates were substantially higher than non-Aboriginal rates in all substrata. Compared with metropolitan people, regional Aboriginal men and very remote non-Aboriginal men aged 25–54 years had significantly higher incidence rates. For the remaining rural strata, there was either no geographical disadvantage or inconclusive findings. Conclusions: Non-metropolitan disadvantage in myocardial infarction rates is confirmed in regional areas and women in very remote areas. This disadvantage is partly explained by the high rates in Aboriginal people. Non-metropolitan dwellers are not uniformly disadvantaged, reflecting the interplay of the many factors contributing to the complex relationship between myocardial infarction incidence and sex, age, Aboriginality and residence. Aboriginal Western Australians in all regions and young non-Aboriginal men living in very remote areas need to be targeted to reduce disparities in myocardial infarction.